Assessment of acute liver toxicity of Trigonella foenum-graecum (fenugreek) seeds aqueous extract in male mice - Alfarisi, Hamad Abdulsalam Hamad (Kulliyyah of Medicine, International Islamic University Malaysia, 2017)
Fenugreek has many uses as herbal medicine, and different fenugreek extraction forms have been tested for therapeutic uses, however data on acute toxicity and safety of fenugreek still not sufficient. Therefore, toxicological evaluation of different forms of fenugreek extracts in experimental animals is a prerequisite for clinical trials, and future therapeutic applications. The objective of this study was to study the acute toxicity (14 days) of fenugreek seeds aqueous extract (FSA) in vivo. Twelve Swiss Albino mice of male gender, aged 6 to 7 weeks, weighing 25 to 26 grams were randomly divided into control (C), and three treated (T1, T2, and T3) groups (n = 3 each). After overnight fasting, T1, T2, and T3 were given 3g, 6g, and 9g/kg body weight FSA respectively. These doses were given as intragastric divided doses as per OECD guidelines 425. After, one hour the mice were allowed to feed. Continuous observation of signs of acute toxicity and survival set up. Body weight was measured every 3 days, blood glucose level was measured 6 hours after the mice have fed, then on days 3, 7, and 14, blood for liver function test was collected twice on days 3 and 14 which is the day of sacrificing the mice. Liver was dissected and processed for histopathological examination. Acute intragastric administration of 9g/kg body weight of FSA showed 66.7% survival rate, while the lower FSA doses showed 100% survival. In all groups FSA at doses of 3, 6, and 9g/kg body weight, failed to induce any signs of acute toxicity. Further, no significant effect shown on mice body weight, blood glucose level and liver biochemical markers such as ALT, AST, ALP, and GGT enzymes. On the other hand, all FSA administered doses showed liver histopathological changes in the form of mild portal inflammation, mild mononuclear cell infiltration in hepatic parenchyma, in addition to mild bile stasis induced only in mice received 9g/kg of FSA, but no steatosis induced in all treated mice groups. In conclusion, FSA showed minimum lethal oral dose of 9g/kg body weight, FSA administered doses, does not produce any significant acute toxicity as reflected by the various investigated parameters apart of mild liver histopathological inflammatory changes which reflect mild liver injury induced by the all FSA tested doses.